Nadgrobna ploča zagrebačkoga biskupa Luke od Segeda (Luke Baratina). - Pelc, Milan (Journal of the Institute of Art History, 2021)
During the primary repairs of the damage caused by the earthquake that struck Zagreb and its surroundings on March 22, 2020, four stone fragments were found in the floor under the pavement in the cathedral apse and promptly identified as parts of the tombstone of Luka de Szeged, also known as Luka Baratin, Bishop of Zagreb from 1500 to 1510. In the previous strong earthquake of 1880, three fragments of the same tombstone had been found, the most impressive being the portrayed head of the late bishop in full sculpture (all three preserved in the Croatian History Museum). Initially, some local experts attributed this work to sculptor Giovanni Dalmata (Ivan Duknović), but recently the Italian sculptor Johannes Fiorentinus, whose workshop in Esztergom produced a number of monuments, primarily tombstones, for various commissioners in the Kingdom of Hungary and beyond, has been acknowledged as the author of the bishop’s tombstone. The four new fragments found in the cathedral significantly complement our knowledge of the appearance and shape of the bishop’s tombstone, confirming the artistic and material unity of its making, as well as its uniqueness within the group of similar tombstones produced in the Kingdom of Hungary at that time. Bishop Luka de Szeged was in close contact with the royal court in Buda during the reign of Vladislaus II, where he held the distinguished service of the king’s treasurer. Staying frequently in Buda, he came into direct contact with the cultural trends at the court and the Renaissance fashion that was spreading from Italy to the Kingdom of Hungary. Artists’ workshops, in which Italian masters had the main say, were established to meet the needs of the royal palace, but they also received commissions from other dignitaries, primarily ecclesiastical and secular magnates who imitated the artistic tastes of the ruler and the court. Bishop Luka commissioned a tombstone for his grave located in a prominent place in the sanctuary of the ecclesia cathedralis, which depicted his figure in full ornate with the coat of arms and an appropriate inscription. Unfortunately, along with the tombstone of other bishops located in the cathedral sanctuary, it was removed during the installation of the new paving in 1703. The tombstones are mentioned in the descriptions of the Zagreb cathedral from the 17th and 18th centuries. The earliest description is that of Canon Rafael Levaković (around 1638), which also brings the tombstone inscription. Due to the finding of new fragments, the inscription can now be almost completely reconstructed. The new find has revealed almost the entire lower part of the bishop’s body in full ornate. It can now be seen that Bishop Luka has a pax on his chest, with three-leafed arm ends. In its centre, there is another, smaller and shallowly carved cross with a regular rhomboid recess, in which a bronze insert of Corpus Christi may have been fixed. This detail coincides with the information from Levaković’s description, according to which the bishop’s coat of arms was made of brass and applied to a stone slab next to his right foot. Unfortunately, these bronze parts of the tombstone have been lost. A newly revealed iconographic detail tells a little more about Bishop Luka and his personal piety. Over the richly embroidered brocade cross of the chasuble, under the bishop’s palms, there is a large medallion encolpion, shown in shallow relief and bordered with gems and pearls, which depicts the Man of Sorrows – imago pietatis. The encolpion is slightly slanted in relation to the cross on the chasuble, below which there is an embroidered medallion with Christ’s monogram IHS, and a little lower Mary’s monogram with the initials AM in Roman capital letters. The encolpion with the imago pietatis hangs on a necklace that descends from the bishop’s neck, passes under the cross, and disappears behind his palms. Judging by the depiction on the tombstone, Bishop Luka owned the encolpion with the Man of Sorrows while still alive, as it gave him hope to shortening his time in the Purgatory, and he wanted to remain united with it in effigie in his eternal rest, considering it a kind of token for the salvation of his soul. As for the preserved tombstones from the late medieval Kingdom of Hungary, a similar encolpion, i.e. medallion depicting the Crucifixion, is attested on the tombstone of Cardinal Dénes Szécsi, Archbishop of Esztergom (d. 1465), preserved in the Esztergom Cathedral. Another example is the tombstone of Briccius Egerváry, a titular Bishop of Knin, situated in the church of St Catherine in Egervár and dating from 1515, where the bishop is wearing a small circular medallion reliquary around his neck – an encolpion with a lid. However, an encolpion with the imago pietatis as that on the tombstone of Bishop Luka, is exceptional not only in Croatian, but also in Central European sepulchral iconography. The medallion with the imago pietatis used as a personalized addition to the representation of the deceased indicates that the bishop commissioned the tombstone himself while still alive. With its main features just described – polished red stone (often indicated as marble) evoking the porphyry of Roman imperial sarcophagi, an inscription plate in the form of a tabula ansata, the image of the deceased in full episcopal ornate, the coat of arms wrought in bronze, exquisite sculptural work by a Florentine master, and the medallion with the Man of Sorrows as a personalized iconographic addition – the tombstone of Bishop Luka de Szeged belongs to the most representative sepulchral monuments known from the former Kingdom of Hungary. For northern Croatia and the (Arch)diocese of Zagreb, it is a first-class monument of Renaissance art, where the humanist spirit intertwines with the traditional symbolism of eschatological expectations of a pious bishop.